2008
DOI: 10.1128/aem.01722-07
|View full text |Cite
|
Sign up to set email alerts
|

Novel Microarray Design Strategy To Study Complex Bacterial Communities

Abstract: Assessing bacterial flora composition appears to be of increasing importance to fields as diverse as physiology, development, medicine, epidemiology, the environment, and the food industry. We report here the development and validation of an original microarray strategy that allows analysis of the phylogenic composition of complex bacterial mixtures. The microarray contains ϳ9,500 feature elements targeting 16S rRNA gene-specific regions. Probe design was performed by selecting oligonucleotide sequences specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(48 citation statements)
references
References 50 publications
1
46
0
1
Order By: Relevance
“…Although high-throughput (or 'nextgeneration') sequencing can detect low-relative-abundance microorganisms in the environment (Andersson et al 2010;Roesch et al 2007), its high cost and complex analysis hinder its large-scale application to monitoring bacterial communities (Kircher and Kelso 2010;Seong Woon et al 2010). The large parallel nature of phylogenetic microarray hybridizations enables rapid identification of bacterial groups and reflection of their changes in the environment (Brodie et al 2006;Huyghe et al 2008). Our result showed that actinobacterial microarray can detect high-relative-abundance actinobacteria and reflect their changes in health as well as in shrimp pond conditions.…”
Section: Pyrosequencing Results Of Water Samplesmentioning
confidence: 77%
“…Although high-throughput (or 'nextgeneration') sequencing can detect low-relative-abundance microorganisms in the environment (Andersson et al 2010;Roesch et al 2007), its high cost and complex analysis hinder its large-scale application to monitoring bacterial communities (Kircher and Kelso 2010;Seong Woon et al 2010). The large parallel nature of phylogenetic microarray hybridizations enables rapid identification of bacterial groups and reflection of their changes in the environment (Brodie et al 2006;Huyghe et al 2008). Our result showed that actinobacterial microarray can detect high-relative-abundance actinobacteria and reflect their changes in health as well as in shrimp pond conditions.…”
Section: Pyrosequencing Results Of Water Samplesmentioning
confidence: 77%
“…For example, DNA microarray chips have been designed to identify 20-100% of the 32 phyla described in the ribosomal database project (RDP). Armed with nearly 9500 probes, this is claimed to be able to identify 78.3% of the RDP sequences (Huyghe et al, 2008). Although the time spent on oral microbe identification is shortened with the use amplification-based clonal analysis, this could be shortened even further by using pyrosequencing.…”
Section: Detecting Oral Bacteria Nb Parahitiyawa Et Almentioning
confidence: 99%
“…Enables the large scale use in comparing bacterial communities in different oral conditions (Huyghe et al, 2008) Pyrosequencing to study the oral bacterial microbiome (saliva and subgingival plaque)…”
Section: Study Scope Main Findings and Remarks Referencesmentioning
confidence: 99%
“…comm.). A similarly large-scale phylochip has subsequently been published and used for oral microbial communities (Huyghe et al, 2008). …”
Section: Previous and Current Microarray Applications In Microbiamentioning
confidence: 99%